CLIMATE CHANGE AND COMMUNITY PERCEPTION: THE CASE STUDY IN MIANG ISLAND VILLAGE, EAST KUTAI : PERUBAHAN IKLIM DAN PERSEPSI MASYARAKAT: STUDI KASUS DI DESA PULAU MIANG, KUTAI TIMUR - Sariasih, Onyhanda Fatma; Arifin, Muhammad (Progress In Social Development, 2026)
The phenomenon of climate change currently occurring not only impacts the environment but also affects human life, especially vulnerable groups whose livelihoods depend on natural resources and environmental conditions, one of which is the maritime community whose life depends on the sea and weather conditions. This study aims to elucidate the complexity of perceptions regarding climate change and environmental degradation from the perspective of the Miang Island community, whose livelihoods depend on the sea, and to analyze the relationship between the community and its environment. This study uses a descriptive qualitative method with a phenomenological type and employs the New Environmental Paradigm theory to understand the relationship between the two. The research results show that community perceptions are formed due to the interaction between the community and the environment, creating an experience that indicates the occurrence of climate change phenomena and forming a traditional knowledge base for the community, assuming that these phenomena refer to the transitional seasons and environmental degradation. Based on that traditional knowledge, the community undertakes adaptation and mitigation efforts that are both physical and socio-cultural, ranging from the tradition of tolak bala to the formation of youth communities aimed at preserving the natural environment on Miang Island. This encourages decision-making that leads to ecological and economic sustainability, prompting the community to be more conservative in their interactions with the environment for the sake of future environmental sustainability. The results of this study can be used by the government as a basis for formulating climate change mitigation policies for island communities.